2014
DOI: 10.1007/s00429-014-0848-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Alzheimer’s disease-linked synapse loss and compensation in mouse and human hippocampal CA1 pyramidal neurons

Abstract: Alzheimer’s disease (AD) is associated with alterations in the distribution, number, and size of inputs to hippocampal neurons. Some of these changes are thought to be neurodegenerative, whereas others are conceptualized as compensatory, plasticity-like responses, wherein the remaining inputs reactively innervate vulnerable dendritic regions. Here, we provide evidence that the axospinous synapses of human AD cases and mice harboring AD-linked genetic mutations (the 5XFAD line) exhibit both, in the form of syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
64
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 116 publications
(177 reference statements)
17
64
2
Order By: Relevance
“…Most synapses presented a simple, macular shape (accounting for 86% of the synapses in all layers of CA1), in agreement with previous reports in different brain areas and species (12,(33)(34)(35)(36).…”
Section: Shape and Size Of The Synapsessupporting
confidence: 92%
“…Most synapses presented a simple, macular shape (accounting for 86% of the synapses in all layers of CA1), in agreement with previous reports in different brain areas and species (12,(33)(34)(35)(36).…”
Section: Shape and Size Of The Synapsessupporting
confidence: 92%
“…However, it is the synaptic and dendritic loss, which seems to be the best predictor of the clinical symptoms. This dysfunction has been extensively described in early studies [ 45 , 57 , 64 ] and confirmed in more recent years [ 17 , 42 , 59 ]. Reduction in spine number correlates well with the degree of memory loss and cognitive impairment of the patients [ 16 ].…”
Section: Introductionmentioning
confidence: 55%
“…Post-embedding immunogold EM Reagents used for EM were from Electron Microscopy Sciences (Hatfield, PA) unless otherwise noted. Tissue was processed as described previously (Neuman et al, 2015). Briefly, mice were perfused transcardially with 4% paraformaldehyde/0.5% glutaraldehyde, after which the hippocampus was dissected and sectioned into 300 mm-thick slices.…”
Section: Confocal Image Acquisition and Quantificationmentioning
confidence: 99%